Plate Assay for Detection of Leptospira interrogans serovar pomona Hemolysin - Stamm, Lola V. (1979)
A plate assay which utilizes the addition of a blood agar overlay for detection of hemolysin by colonies of Leptospira interrogans serovar pomona is described.